Phenolic Compounds from Tobacco Stem - Kong, Wei-Song; Cui, Zhu-Wen; Liu, Wei; Yang, Guang-Yu; Miao, Ming-Ming; Chen, Yong-Kuan (Asian Journal of Chemistry, 2011)
A new phenolic compound (tobphenol A) together with five known phenols was isolated from the tobacco stem. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidences. The anti HIV-1 activity of tobphenol A was also evaluated. It is shown that tobphenol A has moderate anti HIV-1 activity with a therapeutic index (TI) above 128.